A composite material based on covalent-metal organic framework dual carrier and its preparation method and application

By using a covalent-metal-organic framework dual carrier system and a composite material loaded with Ru element, the problem of poor stability and cycleability of existing catalysts in catalyzing the hydrolysis of sodium borohydride to produce hydrogen is solved, achieving efficient catalytic performance and good Cycle performance.

CN116159600BActive Publication Date: 2025-01-21GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211714128.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-01-21
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing catalysts have poor stability, poor circulation and poor conductivity when catalyzing the hydrolysis of sodium borohydride to produce hydrogen, resulting in low catalytic performance.

Method used

A composite material based on a covalent-metal organic framework dual carrier is used, using JUC-505 and ZIF-67 as carriers to load the Ru element to form a Ru-(JUC-505/ZIF-67) composite material, which enhances the conductivity and conductivity of the carrier. Structural stability.

Benefits of technology

The catalytic performance and cycle performance of the catalyst are improved. The maximum hydrogen production rate is 35291mL·min-1·g-1, the hydrogen release amount is 100% of the theoretical value, and the catalytic activation energy is Ea=23.9kJ·mol-1. After 10 cycles, 91.0% of the initial catalytic activity was still retained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116159600B_ABST
    Figure CN116159600B_ABST
Patent Text Reader

Abstract

The invention discloses a composite material based on a covalent metal organic framework dual carrier, which is composed of a JUC-505 covalent organic framework, a ZIF-67 metal organic framework and a Ru element, wherein ZIF-67 is grown on JUC-505 to obtain JUC-505 / ZIF-67 as a dual carrier, and then Ru-(JUC-505 / ZIF-67) is obtained by loading the Ru element, which has magnetism. Raw materials include anhydrous potassium carbonate, tetrafluoroterephthalonitrile, hexahydroxytriphenylene, mesitylene, 1-methylpyrrolidine, hexahydrated cobalt nitrate, 2-methylimidazole, ruthenium trichloride hydrate and a hydrogen-argon mixture. Its preparation method includes the following steps: 1, the preparation of JUC-505; 2, the preparation of JUC-505 / ZIF-67; 3, the preparation of Ru-(JUC-505 / ZIF-67). As a catalyst for hydrogen production from sodium borohydride hydrolysis, the hydrogen production rate provided at 303 K is 25830‑35291 mL∙min ‑1 ∙g ‑1 , the amount of hydrogen released is 100% of the theoretical value, and the activation energy of catalytic hydrogen release is E a =23.9‑30.3 kJ∙mol ‑1 ; At 303 K, 83.2‑91.0% of the initial catalytic activity was retained after 10 recycling / reuses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyzing the hydrolysis of sodium borohydride to produce hydrogen, and in particular to a composite material based on a covalent-metal organic framework dual carrier, and a preparation method and application thereof. Background Art

[0002] NaBH4 in hydrogen energy materials has the advantage of a theoretical hydrogen storage capacity of up to 10.8wt.%, but NaBH4 has the problem of slow hydrolysis at room temperature, and it is necessary to add a catalyst to increase the reaction rate. Currently, the common sodium borohydride hydrolysis hydrogen production catalysts mainly include precious metal-based and non-precious metal-based catalysts.

[0003] Among them, non-precious metal-based catalysts such as Co and Ni have good catalytic performance for the hydrolysis of NaBH4. However, non-precious metal-based catalysts still cannot meet the demand for hydrogen production, and there are technical problems such as large particle size, easy agglomeration and poor cycle stability. Among the precious metals Pt, Pd, Ru and Rh, Ru metal catalysts have higher catalytic activity and better cycle stability.

[0004] For example, in the existing document 1 (Liu Z, Guo B, Chan SH, et al. Pt and Ru dispersed on LiCoO2 for hydrogen generation from sodium borohydride solutions [J]. Journal of Power Sources, 2008, 176 (1): 306-311.), nano-scale Ru dispersed on the surface of LiCoO2 was prepared as a borohydride hydrolysis catalyst by a microwave-assisted polyol method. Since this technical solution has the technical problems of small specific surface area and few pores of the carrier material LiCoO2, the catalytic effect of the catalyst is directly caused, and the hydrogen production rate at 25°C is only 3000 mL min -1 ·g -1 .

[0005] The above technical problems can be solved by compounding with porous carrier materials with large specific surface areas. Metal-organic frameworks (MOFs) are a type of crystalline porous materials that have the advantages of being able to confine metals, having high specific surface areas, and having diverse structures.

[0006] For example, in the existing literature 2 (Tuan DD, Lin KY A. Ruthenium supported on ZIF-67 as an enhanced catalyst for hydrogen generation from hydrolysis of sodium borohydride [J]. Chemical Engineering Journal, 2018, 351: 48-55.), Ru / ZIF-67 nanopowder catalyst was synthesized by chemical reduction method. The hydrogen production performance of Ru / ZIF-67 catalyzing the hydrolysis of NaBH4 is better than that of Ru. Ru-9.0 / ZIF can reach 5520 mL·min at 30°C. -1 ·g -1 and 22,400 mL·min at 60°C -1 ·g -1 . This technical solution proves that MOFs materials can improve catalytic performance, but there are still the following technical problems: when a single MOFs material is used as a carrier, the catalytic performance is low and the cyclability is poor; in addition, MOFs materials generally have poor structural stability and are easily decomposed under air, water vapor, acid, alkali or heat conditions, causing skeleton collapse. To address this technical problem, a dual-carrier system can be used, that is, by compounding another carrier to improve the stability of the catalyst.

[0007] Among them, covalent organic frameworks (COFs) are a type of stable crystalline porous materials, which are composed of lightweight organic molecular units connected by covalent bonds to form a two-dimensional or three-dimensional network structure. They have the advantages of excellent thermal stability, large specific surface area and diverse pore sizes. However, COFs materials only contain light elements such as C, H, O, and N, do not contain metals, and have poor conductivity. Therefore, a single COFs carrier cannot promote electron transfer in catalysis.

[0008] Based on the above analysis, it can be seen that COFs and MOFs each have inherent defects, namely the following technical problems:

[0009] 1. When a single MOFs material is used as a carrier, the stability and cyclability are poor;

[0010] 2. When a single COFs material is used as a carrier, it has poor conductivity and cannot promote electron transfer during the catalytic process.

[0011] However, according to the research of the present invention, it can be known that preparing MOFs materials and COFs materials into a dual-carrier system can achieve the effect of complementing each other's strengths and weaknesses, using their respective advantages to make up for each other's shortcomings, that is, while enhancing the conductivity of the carrier, the thermal stability of the carrier is enhanced, and ultimately the catalytic performance and cycle performance of the composite catalyst are improved.

[0012] It should be noted that, according to the currently available literature, there is no technical solution for applying COFs materials to NaBH4 hydrolysis.

[0013] Purpose of the Invention

[0014] The purpose of the present invention is to provide a composite material based on a covalent-metal organic framework dual carrier and a preparation method and application thereof.

[0015] The present invention aims at solving the technical problems existing in the prior art by adopting the following principles and methods:

[0016] 1. By loading Ru elements on dual carriers, the microstructure is homogenized to avoid agglomeration, thereby effectively increasing the contact area between Ru and NaBH4 and ultimately improving the catalytic performance;

[0017] 2. There is a synergistic effect between the two carriers, which improves the structural stability of the material.

[0018] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0019] A composite material based on a covalent metal organic framework dual carrier is composed of a JUC-505 covalent organic framework, a ZIF-67 metal organic framework and a Ru element, wherein ZIF-67 is grown on JUC-505 to obtain JUC-505 / ZIF-67 as a dual carrier, and then the Ru element is loaded to obtain a Ru-(JUC-505 / ZIF-67) composite material based on a covalent metal organic framework dual carrier, referred to as Ru-(JUC-505 / ZIF-67;

[0020] The raw materials for preparing the JUC-505 are anhydrous potassium carbonate, tetrafluoroterephthalonitrile, hexahydroxytriphenylene, mesitylene and 1-methylpyrrolidone; the raw materials for preparing the ZIF-67 are cobalt nitrate hexahydrate and 2-methylimidazole; the raw materials for loading the Ru element are ruthenium trichloride hydrate and hydrogen-argon mixed gas;

[0021] The obtained Ru-(JUC-505 / ZIF-67) has magnetic properties.

[0022] A method for preparing a composite material based on a covalent-metal organic framework dual carrier comprises the following steps:

[0023] Step 1, preparation of JUC-505, first, 2,3,6,7,10,11-hexahydroxytriphenylene and tetrafluoroterephthalonitrile are ground and mixed to obtain a mixture A; then, the obtained mixture A, anhydrous potassium carbonate, mesitylene and 1-methylpyrrolidone are mixed to obtain a mixture B; then, the mixture B is degassed; after the degassed operation is completed, the mixture is reacted under certain conditions under vacuum conditions; finally, the reaction product is soaked and washed, solvent exchanged, filtered and vacuum dried to obtain JUC-505;

[0024] In the step 1, 2,3,6,7,10,11-hexahydroxytriphenylene, tetrafluoroterephthalonitrile, anhydrous potassium carbonate, mesitylene and 1-methylpyrrolidone satisfy the following ratios: 1 mol: (0.5-2) mol: (0.5-10) mol: 0.2 L: (0.05-0.8) L;

[0025] In step 1, the reaction conditions are: the reaction temperature is 120-180° C., and the reaction time is 3-7 days;

[0026] The degassing operation is to first freeze with liquid nitrogen, then evacuate, and finally melt, and the degassing operation is repeated 3-5 times;

[0027] The soaking and washing method is to soak and wash in N, N-dimethylformamide, water and tetrahydrofuran in sequence, the solvent is replaced with acetone, and the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-12 hours;

[0028] Step 2, preparation of JUC-505 / ZIF-67, placing the JUC-505 obtained in step 1 and cobalt nitrate hexahydrate in methanol, performing an operation of first ultrasonication and then standing to obtain a mixture C; in addition, placing 2-methylimidazole in methanol to obtain a mixture D; then quickly adding the mixture D to the mixture C, performing an operation of first stirring and then standing to obtain a product A; finally, centrifuging the obtained product A under certain conditions, and then vacuum drying under certain conditions to obtain JUC-505 / ZIF-67;

[0029] In the step 2, the mass ratio of JUC-505, cobalt nitrate hexahydrate, and 2-methylimidazole satisfies (1-4): 60: (20-40);

[0030] In the step 2, the conditions for the operation of first ultrasonicating and then standing to obtain the mixture C are: the ultrasonic time is 0.5-1h, and the standing time is 12-24h; the conditions for the operation of first stirring and then standing to obtain the product A are: the stirring time is 2-3h, and the standing time is 12-24h; the conditions for centrifugation are: the centrifugal speed is 5000-6000r / min, and the centrifugal time is 5-6min; the conditions for vacuum drying are: the drying temperature is 60-80°C, and the drying time is 6-12h;

[0031] Step 3, preparation of Ru-(JUC-505 / ZIF-67), after dispersing the JUC-505 / ZIF-67 obtained in step 2 in deionized water, adding ruthenium trichloride hydrate, performing an operation of first ultrasonication and then standing to obtain product B, the obtained product B is filtered, vacuum dried under certain conditions, and finally reduced under certain conditions under 5% hydrogen and argon mixed gas conditions, and cooled to room temperature after the reduction is completed, so as to obtain a Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier, referred to as Ru-(JUC-505 / ZIF-67);

[0032] In the step 3, the mass ratio of JUC-505 / ZIF-67 to ruthenium trichloride hydrate satisfies 1:(0.04-0.1);

[0033] In step 3, the conditions for the ultrasonication followed by the standing operation to obtain the product B are: the ultrasonication time is 0.5-1h, and the standing time is 12-24h; the vacuum drying conditions are: the drying temperature is 60-80°C, and the drying time is 6-12h; the conditions for the reduction by the hydrogen-argon mixed gas are: the reduction temperature is 200-500°C, and the heating rate is 5°C·min -1 , the reduction time is 4-5h.

[0034] As a catalyst for hydrogen production from sodium borohydride hydrolysis, the hydrogen production rate provided at 303K is 25830-35291mL·min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value, and the activation energy of catalytic hydrogen release is E a =23.9-30.3 kJ·mol -1 ; At 303K, after 10 recycling / reuses, 83.2-91.0% of the initial catalytic activity was retained.

[0035] The technical effects of the present invention have been tested and the specific contents are as follows:

[0036] The present invention has been tested by SEM and found that: the Ru-(JUC-505 / ZIF-67) material presents a uniform composite morphology of rhombic dodecahedron and small grains;

[0037] The present invention has successfully synthesized Ru-(JUC-505 / ZIF-67) material through XRD detection;

[0038] The present invention is tested by EDS and it can be seen that the Ru, Co, C, N and O elements are evenly distributed in the Ru-(JUC-505 / ZIF-67) material;

[0039] The present invention has been found through magnetic detection that: Ru-(JUC-505 / ZIF-67) material is a magnetic material;

[0040] The maximum hydrogen production rate provided by the invention at 303K is 35291 mL·min -1 ·g -1 ;

[0041] The present invention has been tested for reaction kinetics and found that the apparent activation energy E of the reaction is a =23.9 kJ·mol -1 ;

[0042] The cyclic performance test of the present invention shows that after 10 cycles at 303K, 91.0% of the initial catalytic activity for the hydrolysis of NaBH4 is still retained.

[0043] Therefore, the present invention has the following advantages through SEM, XRD, EDS and other experimental tests:

[0044] 1. The present invention uses a dual-carrier composite catalytic system, namely JUC-505 and ZIF-67 as carriers, which enhances the adhesion of the supported particles and enhances the cycle stability;

[0045] 2. The present invention combines JUC-505 and ZIF-67 with large specific surface areas to generate a dual-carrier material with uniform morphology, inhibiting agglomeration and effectively increasing the contact area between metal Ru and NaBH4, thereby increasing the hydrogen production rate of the catalyst;

[0046] 3. The JUC-505 / ZIF-67 dual-carrier structure effectively avoids problems such as structural collapse and falling off, ensuring the stability of the catalyst during the reaction.

[0047] 4. The present invention has magnetism, and magnetic recovery replaces the traditional suction filtration recovery method, which can effectively improve the problems of oxidation and shedding during its use, greatly reduce the process difficulty of the recovery process and the damage to the microscopic morphology of the material, and improve the stability of the catalyst.

[0048] 5. The raw materials used in the present invention are all industrially produced chemical raw materials, which are available in the market and easy to obtain. The process for synthesis is simple, the reaction cycle is short, the reaction process has low energy consumption and low pollution.

[0049] 6. As a catalytic hydrogen production material, the Ru-(JUC-505 / ZIF-67) dual-carrier composite material based on covalent metal organic framework has high efficiency in catalyzing the hydrolysis of sodium borohydride to produce hydrogen, and the maximum hydrogen production rate provided at 303K is 35291mL·min -1 g -1 ; The amount of hydrogen released is 100% of the theoretical value; The activation energy of catalytic hydrogen release is Ea = 23.9 kJ·mol-1;

[0050] 7. As a catalytic hydrogen production material, the Ru-(JUC-505 / ZIF-67) dual-carrier composite material based on covalent metal organic framework has excellent cycling performance. After 10 cycles at 298K, it still retains 91.0% of its initial catalytic activity for NaBH4 hydrolysis.

[0051] Therefore, compared with the prior art, the present invention has better catalytic performance for producing hydrogen by hydrolysis of sodium borohydride, improves the stability of the catalyst, and has broad application prospects in the fields of hydrogen production materials, fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 X-ray diffraction patterns of JUC-505, ZIF-67, JUC-505 / ZIF-67 and Ru-(JUC-505 / ZIF-67) in Example 1;

[0053] Figure 2 is a scanning electron microscope image of JUC-505 in Example 1;

[0054] Figure 3 is a scanning electron microscope image of JUC-505 / ZIF-67 in Example 1;

[0055] Figure 4 is the backscattered electron image of Ru-(JUC-505 / ZIF-67) in Example 1;

[0056] Figure 5 The EDS image corresponding to the backscattered electron image of Ru-(JUC-505 / ZIF-67) in Example 1;

[0057] Figure 6 is a scanning electron microscope image of Ru-(JUC-505 / ZIF-67) in Example 1;

[0058] Figure 7 The Ru-(JUC-505 / ZIF-67) catalyzes the hydrolysis and hydrogenation of sodium borohydride at different temperatures in Example 1;

[0059] Figure 8is the activation energy diagram of Ru-(JUC-505 / ZIF-67) in Example 1;

[0060] Fig. 9 This is a picture of Ru-(JUC-505 / ZIF-67) adsorbed on the surface of a magnetic stirring bar in the cycle test of Example 1;

[0061] Fig.10 The cycle performance diagram of Ru-(JUC-505 / ZIF-67) in Example 1 after catalyzing sodium borohydride hydrolysis and hydrogenation for 10 cycles at 303K;

[0062] Fig.11 is a scanning electron microscope image of Ru / ZIF-67 in Comparative Example 1;

[0063] Fig.12 It is a comparison chart of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 catalyzing the hydrolysis and hydrogenation of sodium borohydride at a temperature of 303K;

[0064] Fig.13 This is a scanning electron microscope image of Ru / JUC-505 in Comparative Example 2. DETAILED DESCRIPTION

[0065] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0066] Example 1

[0067] A method for preparing a composite material based on a covalent-metal organic framework dual carrier, the specific steps are as follows:

[0068] Step 1, preparation of JUC-505, first, 32.4 mg of 2,3,6,7,10,11-hexahydroxytriphenylene and 30.0 mg of tetrafluoroterephthalonitrile are ground and mixed to obtain a mixture A; then, the obtained mixture A, 138.2 mg of anhydrous potassium carbonate, 0.3 mL of mesitylene and 0.6 mL of 1-methylpyrrolidone are mixed to obtain a mixture B; then, the mixture B is degassed; after the degassing operation is completed, the reaction is carried out under vacuum conditions at a reaction temperature of 120° C. and a reaction time of 3 days; finally, the reaction product is subjected to soaking washing, solvent exchange, suction filtration and vacuum drying to obtain JUC-505;

[0069] The degassing operation is to first freeze with liquid nitrogen, then evacuate, and finally melt, and the degassing operation is repeated 3 times;

[0070] The soaking and washing method is to soak and wash in N, N-dimethylformamide, water and tetrahydrofuran in sequence, the solvent is replaced with acetone, and the vacuum drying conditions are as follows: the drying temperature is 80° C. and the drying time is 6 hours;

[0071] In order to prove the composition of JUC-505 obtained in step 1, XRD test was performed. The test results are as follows Figure 1 As shown, the standard peak of JUC-505 is consistent with that of JUC-505 reported in the literature. The test results show that JUC-505 was successfully synthesized.

[0072] In order to verify the microstructure of the material JUC-505 obtained in step 1, SEM test was performed. The test results are as follows Figure 2 As shown, JUC-505 is in the form of small grains with uniform size.

[0073] Step 2, preparation of JUC-505 / ZIF-67, the JUC-505 obtained in step 1 and 1.0275g of cobalt nitrate hexahydrate are placed in 80mL of methanol, and an operation of ultrasonication is performed for 30min and standing for 24h to obtain a mixture C; in addition, 2.32g of 2-methylimidazole is placed in 80mL of methanol to obtain a mixture D; then the mixture D is quickly added to the mixture C, and the operation of stirring for 3h and standing for 24h is performed to obtain a product A; finally, the obtained product A is centrifuged at a centrifugal speed of 6000r / min and a centrifugal time of 5min, and then vacuum dried at a drying temperature of 60°C and a drying time of 12h to obtain JUC-505 / ZIF-67;

[0074] In order to prove the composition of JUC-505 / ZIF-67 obtained in step 2, XRD test was performed. The test results are as follows Figure 1 As shown, the diffraction peak at 4.25° is the characteristic peak of JUC-505, and the other diffraction peaks are the characteristic peaks of ZIF-67. The test results show that JUC-505 and ZIF-67 are successfully composited.

[0075] In order to verify the microstructure of JUC-505 / ZIF-67 obtained in step 2, SEM test was performed. The test results are shown in Figure 3 As shown, rhombic dodecahedral ZIF-67 is grown on the small JUC-505 grains obtained in step 1. The test results show that ZIF-67 is loaded on JUC-505 by step 2.

[0076] Step 3, preparation of Ru-(JUC-505 / ZIF-67), 0.25 g of JUC-505 / ZIF-67 obtained in step 2 was dispersed in deionized water, 15 mg of ruthenium trichloride hydrate was added, and the product B was obtained by ultrasonication for 30 min and standing for 24 h. Then, the obtained product B was filtered and vacuum dried at a drying temperature of 60° C. and a drying time of 12 h. Finally, under the condition of 5% hydrogen-argon mixed gas, the reduction temperature was 300° C. and the heating rate was 5° C. min -1 The reduction was carried out under the condition of a reduction time of 4 hours and cooled to room temperature after the reduction was completed to obtain a Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier, referred to as Ru-(JUC-505 / ZIF-67).

[0077] In order to verify the composition of Ru-(JUC-505 / ZIF-67) obtained in step 3, XRD test was performed. The test results are shown in Figure 1 As shown in Figure 3, after loading Ru nanoparticles, the characteristic peaks of JUC-505 / ZIF-67 did not shift, and no characteristic peaks of Ru nanoparticles were found. The test results show that loading Ru nanoparticles has no effect on the crystal structure; in addition, since the content of Ru nanoparticles is below the detection limit and cannot be detected, the EDS test is supplemented to prove the presence of Ru element.

[0078] The backscattered electron image and EDS test results of Ru-(JUC-505 / ZIF-67) are shown in Figure 4 , Figure 5 As shown, C, O, N, Co and Ru elements are uniformly distributed. The test results show that Ru nanoparticles are successfully loaded on Ru-(JUC-505 / ZIF-67).

[0079] In order to verify the microstructure of Ru-(JUC-505 / ZIF-67) obtained in step 3, SEM test was performed. The test results are shown in Figure 6 As shown, the microstructure of Ru-(JUC-505 / ZIF-67) has no significant change compared with JUC-505 / ZIF-67. The test results show that the process of loading Ru nanoparticles in step 3 has no effect on the microstructure of JUC-505 / ZIF-67.

[0080] In order to prove the hydrogen production performance of Ru-(JUC-505 / ZIF-67) obtained in step 3 as a catalyst for hydrogen production by hydrolysis of sodium borohydride, a hydrogen production by hydrolysis test was conducted. The specific method of the hydrogen production by hydrolysis test is as follows: the hydrogen production test is conducted under the temperature conditions set in the experiment, a solution containing 1.5wt.% NaBH4 and 5wt.% NaOH is placed in a constant temperature water bath, and after reaching equilibrium at the aforementioned set temperature; 10mL is taken out and added to a wide-mouth bottle containing the catalyst, and the volume of hydrogen produced per unit time is collected and recorded by the drainage method, and the hydrogen release rate can be obtained, wherein the temperature condition is 303K when not specifically stated.

[0081] The test results of hydrogen production by hydrolysis of Ru-(JUC-505 / ZIF-67) are shown in Table 1 and Figure 7 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 35290.96 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value.

[0082] Table 1 Hydrogen production rate and activation energy of NaBH4 hydrolysis catalyzed by different catalysts

[0083]

[0084] Note: The reference numbers in Table 1 correspond to the following documents:

[0085] [1]Wei Y,Wang Y,Wei L,et al.Highly efficient and reactivatedelectrocatalyst of ruthenium electrodeposited on nickel foam for hydrogenevolution from NaBH4 alkaline solution.International journal of hydrogenenergy,2018,43(2):592-600.

[0086] [2]Liang Y, Dai HB, Ma LP, et al. Hydrogen generation from sodiumborohydride solution using a ruthenium supported on graphitecatalyst. International journal of hydrogen energy, 2010, 35(7): 3023-3028.

[0087] [3]Bozkurt G.,Ozer A.,Yurtcan ABDevelopment of effective catalysts for hydrogen generation from sodium borohydride:Ru,Pt,Pd nanoparticlessupported on Co3O4.Energy,2019,180,702-713.

[0088] [4]Dinh TD,Andrew K Y.Ruthenium supported on ZIF-67as an EnhancedCatalyst for Hydrogen Generation from Hydrolysis of Sodium Borohydride[.Chemical Engineering Journal, 2018,351:48-55.

[0089] [5] Zhang J, Hao J, Ma Q, et al. Polyvinylpyrrolidone stabilized-Runanoclusters loaded onto reduced graphene oxide as high active catalyst for hydrogen evolution. Journal of Nanoparticle Research, 2017, 19(6): 1-10.

[0090] Furthermore, in order to prove the reaction kinetics of Ru-(JUC-505 / ZIF-67), hydrolysis and hydrogen production tests were carried out at 298K, 308K, and 313K. The test results were fitted by the Arrhenius equation as shown in Table 1 and Figure 8 As shown, the apparent activation energy of the reaction E a =23.93 kJ·mol -1 At the same time, in order to compare with the prior art, the data of the references are summarized in Table 1.

[0091] The following conclusions can be drawn from the above test results and comparative analysis with existing references:

[0092] 1. By comparing with the technical solutions of references [1], [2], [3] and [4], which respectively use Ni, G, Co3O4, and ZIF-67 as carriers of Ru nanoparticles, it can be seen that the dual-carrier composite material of the present invention has a higher hydrogen production rate and a lower activation energy. This phenomenon shows that the dual-carrier composite material can effectively improve the catalytic performance;

[0093] 2. By comparing with the technical solution of reference [4] using Ru-4.0 / ZIF67 as a hydrogen production catalyst, it can be seen that the hydrolysis hydrogen production performance of the catalyst of the present invention is 5.8 times that of reference [4]. This phenomenon shows that the introduction of JUC-505 carrier can greatly improve the catalytic performance;

[0094] 3. By comparing with the technical solution of Ru-PVP / rGO catalyst with PVP / rGO dual carrier in reference [5], it can be seen that the hydrolysis hydrogen production performance of the dual carrier catalyst of the present invention is 2.4 times that of reference [5]. This phenomenon shows that there is a synergistic effect between the JUC-505 / ZIF-67 dual carriers of the present invention.

[0095] Based on the above analysis, the catalytic performance of the present invention is significantly improved compared with the prior art. The reasons are as follows:

[0096] 1. The synergistic effect between the JUC-505 material and the ZIF-67 material in the JUC-505 / ZIF-67 dual carrier of the present invention is excellent, so that the hydrogen production rate of the catalyst is improved;

[0097] 2. The JUC-505 / ZIF-67 dual-carrier system of the present invention improves the uniformity of the material while also inhibiting the agglomeration of the material, effectively increasing the contact area between the Ru nanoparticles and NaBH4, thereby increasing the hydrogen production rate of the catalyst.

[0098] According to the inventor's research results, the recycling performance of the catalyst can be effectively improved by magnetic recovery of the catalyst. Therefore, in order to prove that Ru-(JUC-505 / ZIF-67) has magnetic properties, magnetic tests were conducted. The test results are as follows: Fig. 9 As shown, Ru-(JUC-505 / ZIF-67) is adsorbed on the surface of the magnetic stirring bar. The test results show that Ru-(JUC-505 / ZIF-67) has magnetic properties, that is, the catalyst can be recovered by magnetic force.

[0099] In order to prove the cycle performance of Ru-(JUC-505 / ZIF-67), a cycle performance test was conducted. The specific method of the cycle performance test is: after the Ru-(JUC-505 / ZIF-67) that has been subjected to the hydrogen release test is recovered by magnetic force, the aforementioned hydrolysis hydrogen production test is performed again to obtain the hydrogen release rate after the cycle, and the cycle performance of Ru-(JUC-505 / ZIF-67) can be obtained by simple calculation. The test results are shown in Table 2 and Fig.10 As shown in Figure 2, after 10 cycles at 303 K, 90.96% of the initial catalytic activity is still retained. At the same time, in order to compare with the prior art, the data of the references are summarized in Table 2.

[0100] Table 2 Cycle number and cycle performance of NaBH4 hydrolysis catalyzed by different catalysts

[0101]

[0102] Note: The reference numbers in Table 2 correspond to the following documents:

[0103] [6] Li T, Xiang C, Chu H, et al. Catalytic effect of highly dispersedultrafine Ru nanoparticles on a TiO2-Ti3C2 support: Hydrolysis of sodiumborohydride for H2 generation. Journal of Alloys and Compounds, 2022,906:164380.

[0104] [7] Zhou S, Yang Y, Zhang W, et al. Structure-regulated Ru particles decorated P-vacancy-rich CoP as a highly active and durable catalyst for NaBH4 hydrolysis. Journal of Colloid and Interface Science, 2021, 591: 221-228.

[0105] [8]Rakap M.Hydrolysis of sodium borohydride and ammonia borane forhydrogen generation using highly efficient poly(N-vinyl-2-pyrrolidone)-stabilized Ru-Pd nanoparticles as catalysts.International journal of greenenergy,2015,12(12):1288-1300.

[0106] [9] Doherty S, Knight JG, Alharbi HY, et al. Efficient hydrolytichydrogen evolution from sodium borohydride catalyzed by polymer immobilizedionic liquid-stabilized platinum nanoparticles. ChemCatChem, 2022, 14(4):e202101752.

[0107] As shown in Table 2, the present invention retains 97.6% of the initial catalytic activity after 5 recyclings and 91.0% after 10 recyclings. Compared with references [6]-[9], the cycle performance of Ru-(JUC-505 / ZIF-67) is significantly better after repeated use.

[0108] Based on the above analysis, it can be seen that the significant improvement in the cycle performance of the present invention can be attributed to the following reasons:

[0109] 1. The polyarylether covalent organic framework JUC-505 has excellent stability and can maintain structural stability under conditions such as strong acid, strong base, strong reducing agent or strong oxidizing agent. It can be combined with the stable metal organic framework ZIF-67 to form a dual carrier material, which effectively enhances the structural stability of the catalyst;

[0110] 2. The JUC-505 / ZIF-67 dual-carrier system constructed by the present invention can inhibit the agglomeration of materials during the composite process and improve the cyclic stability of the catalyst during the reaction process;

[0111] 3. The JUC-505 / ZIF-67 dual-carrier loaded Ru nanoparticle catalyst is magnetic, which allows it to be quickly recovered using a magnetic stirrer during the cyclic test, reducing the mass loss and morphological damage of Ru-(JUC-505 / ZIF-67) during the cycle, and effectively improving the cyclic stability of the catalyst during the reaction.

[0112] The characterization and testing of Example 1 proves that the dual carrier improves the technical effect. In order to further prove the respective roles of ZIF-67 and JUC-505 in the technical solution among the dual carriers, Comparative Examples 1 and 2 are provided, in which ZIF-67 and JUC-505 are used as carriers, respectively, and Ru nanoparticles are loaded as catalysts for comparison.

[0113] Comparative Example 1

[0114] A method for preparing a catalyst based on a single carrier ZIF-67, wherein the steps not specifically described are the same as those in Example 1, except that step 1 is not performed, and JUC-505 is not added in step 2. The obtained material is a catalyst based on a single carrier ZIF-67, referred to as Ru / ZIF-67.

[0115] The SEM test results of Ru / ZIF-67 are shown in Fig.11 As shown, Ru / ZIF-67 presents rhombuses of uneven sizes. The test results show that by compounding with JUC-505, the uniformity of the composite material can be improved, that is, the microstructure of the composite material can be adjusted.

[0116] The test results of Ru / ZIF-67 hydrolysis hydrogen production are as follows Fig.12 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 2510.6 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. By comparing with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 15 times compared with Comparative Example 1.

[0117] Comparative Example 2

[0118] A method for preparing a catalyst based on a single carrier JUC-505, wherein the steps not specifically described are the same as those in Example 1, except that step 2 is not performed, and in step 3, JUC-505 is directly added instead of JUC-505 / ZIF-67. The obtained material is a catalyst based on a single carrier JUC-505, referred to as Ru / JUC-505.

[0119] The SEM test results of Ru / JUC-505 are as follows Fig.13As shown, Ru / JUC-505 is a grain agglomerate. The test results show that by compounding with JUC-505, the agglomeration phenomenon of the composite material can be avoided, that is, the microstructure of the composite material can be adjusted.

[0120] The test results of Ru / JUC-505 hydrolysis hydrogen production are as follows Fig.13 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 3793.6 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. By comparing with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 9.3 times compared with Comparative Example 2.

[0121] It can be seen from Comparative Examples 1 and 2 that the catalyst prepared by a single carrier will have problems of uneven morphology and agglomeration. Compared with Example 1, it can be seen that the dual-carrier system used in the present invention has a more uniform and dispersed microscopic morphology. This technical effect directly and effectively increases the contact area between the catalyst and NaBH4 and improves the hydrogen production rate of the catalyst.

[0122] In order to demonstrate the effect of the amount of JUC-505 added on the catalytic performance, comparative examples 3, 4 and 5 are provided, namely, composite catalysts with the amount of JUC-505 added being 50 mg, 100 mg and 200 mg, respectively.

[0123] Comparative Example 3

[0124] A method for preparing a composite catalyst with a JUC-505 addition amount of 50 mg, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 2, the addition amount of JUC-505 is 50 mg, and the obtained composite catalyst is referred to as Ru / JUC-505-50@ZIF-67.

[0125] The test results of Ru / JUC-505-50@ZIF-67 for hydrogen production by hydrolysis are as follows Fig.13 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 25920 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. By comparing with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 36.2% compared with Comparative Example 3.

[0126] Comparative Example 4

[0127] A composite catalyst with 100 mg of JUC-505 added was prepared. The steps not specifically described were the same as those in Example 1, except that 100 mg of JUC-505 was added in step 2, and the obtained material was recorded as Ru / JUC-505-100@ZIF-67.

[0128] The test results of hydrogen production by hydrolysis of Ru / JUC-505-100@ZIF-67 are as follows Fig.13 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 30765 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. By comparing with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 14.7% compared with Comparative Example 4.

[0129] Comparative Example 5

[0130] A composite catalyst with 200 mg of JUC-505 added was prepared. The steps not specifically described were the same as those in Example 1, except that 200 mg of JUC-505 was added in step 2, and the obtained material was recorded as Ru / JUC-505-200@ZIF-67.

[0131] The test results of hydrogen production by hydrolysis of Ru / JUC-505-200@ZIF-67 are as follows Fig.13 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 25831 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. By comparing with Example 1, it can be seen that the hydrogen production performance of Example 1 is improved by 36.6% compared with Comparative Example 5.

[0132] It can be seen from Comparative Examples 3, 4 and 5 that the amount of JUC-505 added has a significant effect on the catalytic performance. Specifically, it can be simply summarized as follows: as the amount of JUC-505 added increases, the morphology of the Ru-(JUC-505 / ZIF-67) composite material becomes uniform and its catalytic performance is enhanced; when the amount of JUC-505 added is 150 mg, the catalytic performance of the catalyst is the best; if JUC-505 is continued to be added, the conductivity of the composite material deteriorates and the catalytic performance of the catalyst decreases.

Claims

1. A composite material based on a covalent-metal organic framework dual carrier, characterized in that: The invention is composed of a JUC-505 covalent organic framework, a ZIF-67 metal organic framework and Ru elements, wherein ZIF-67 is grown on JUC-505 to obtain JUC-505 / ZIF-67 as a dual carrier, and then Ru elements are loaded to obtain a Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier, referred to as Ru-(JUC-505 / ZIF-67); The raw materials for preparing the JUC-505 are anhydrous potassium carbonate, tetrafluoroterephthalonitrile, hexahydroxytriphenylene, mesitylene and 1-methylpyrrolidone; the raw materials for preparing the ZIF-67 are cobalt nitrate hexahydrate and 2-methylimidazole; the raw materials for loading the Ru element are ruthenium trichloride hydrate and hydrogen-argon mixed gas; The obtained Ru-(JUC-505 / ZIF-67) has magnetic properties.

2. A method for preparing a composite material based on a covalent-metal organic framework dual carrier, characterized in that The following steps are involved: Step 1, preparation of JUC-505, first, 2,3,6,7,10,11-hexahydroxytriphenylene and tetrafluoroterephthalonitrile are ground and mixed to obtain a mixture A; then, the obtained mixture A, anhydrous potassium carbonate, mesitylene and 1-methylpyrrolidone are mixed to obtain a mixture B; then, the mixture B is degassed; after the degassed operation is completed, the mixture is reacted under certain conditions under vacuum conditions; finally, the reaction product is soaked and washed, solvent exchanged, filtered and vacuum dried to obtain JUC-505; In the step 1, 2,3,6,7,10,11-hexahydroxytriphenylene, tetrafluoroterephthalonitrile, anhydrous potassium carbonate, mesitylene and 1-methylpyrrolidone satisfy the following ratio relationship: 1 mol: (0.5-2) mol: (0.5-10) mol: 0.2 L: (0.05-0.8) L; In the step 1, the reaction conditions are as follows: the reaction temperature is 120-180° C. and the reaction time is 3-7 days; the degassing operation is as follows: first, liquid nitrogen freezing is performed, then vacuumization is performed, and finally, melting is performed, and the degassing operation is repeated 3-5 times; the soaking and washing method is as follows: soaking and washing with N,N-dimethylformamide, water and tetrahydrofuran in sequence, the solvent is exchanged with acetone, and the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-12 hours; Step 2, preparation of JUC-505 / ZIF-67, placing the JUC-505 obtained in step 1 and cobalt nitrate hexahydrate in methanol, performing an operation of first ultrasonication and then standing to obtain a mixture C; in addition, placing 2-methylimidazole in methanol to obtain a mixture D; then quickly adding the mixture D to the mixture C, performing an operation of first stirring and then standing to obtain a product A; finally, centrifuging the obtained product A under certain conditions, and then vacuum drying under certain conditions to obtain JUC-505 / ZIF-67; In the step 2, the mass ratio of JUC-505, cobalt nitrate hexahydrate, and 2-methylimidazole satisfies (1-4):60:(20-40); In the step 2, the conditions for the operation of first ultrasonicating and then standing to obtain the mixture C are: the ultrasonic time is 0.5-1h, and the standing time is 12-24h; the conditions for the operation of first stirring and then standing to obtain the product A are: the stirring time is 2-3h, and the standing time is 12-24h; the conditions for centrifugation are: the centrifugal speed is 5000-6000r / min, and the centrifugal time is 5-6min; the conditions for vacuum drying are: the drying temperature is 60-80°C, and the drying time is 6-12h; Step 3, preparation of Ru-(JUC-505 / ZIF-67), after dispersing the JUC-505 / ZIF-67 obtained in step 2 in deionized water, adding ruthenium trichloride hydrate, performing an operation of first ultrasonication and then standing to obtain product B, the obtained product B is filtered, vacuum dried under certain conditions, and finally reduced under certain conditions under 5% hydrogen and argon mixed gas conditions, and cooled to room temperature after the reduction is completed, so as to obtain a Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier, referred to as Ru-(JUC-505 / ZIF-67); In the step 3, the mass ratio of JUC-505 / ZIF-67 to ruthenium trichloride hydrate satisfies 1:(0.04-0.1); In step 3, the conditions for the ultrasonication followed by the standing operation to obtain product B are: the ultrasonication time is 0.5-1h, and the standing time is 12-24h; the vacuum drying conditions are: the drying temperature is 60-80°C, and the drying time is 6-12h; the conditions for the reduction by hydrogen-argon mixed gas are: the reduction temperature is 200-500°C, and the heating rate is 3-5°C·min -1 , the reduction time is 4-5h.

3. The use of the Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier as a catalyst for hydrogen production by hydrolysis of sodium borohydride according to claim 1, characterized in that: The hydrogen production rate provided at 303K is 25830-35291mL·min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value, and the activation energy of catalytic hydrogen release is E a =23.9-30.3 kJ·mol -1 .

4. The use of the Ru-(JUC-505 / ZIF-67) composite material based on a covalent-metal organic framework dual carrier as a catalyst for hydrogen production by hydrolysis of sodium borohydride according to claim 1, characterized in that: At 303 K, 83.2–91.0% of the initial catalytic activity was retained after 10 recycling / reuses.